PERTANGGUNG JAWABAN PIDANA SEBAGAI DAMPAK PENUNTUTAN TERHADAP KORPORASI AKIBAT PAILIT - Evy Febryani; Dian Puspa Iwari; Aprita, Serlika (Collegium Studiosum Journal, 2024)
In practice, it is very difficult to determine whether there is or is not a fault in a corporation. It turns out that in developments, especially regarding corporate criminal liability, it is known that there is a new view or let's say a slightly different view, that specifically the responsibility of legal entities, the principle of fault does not absolutely apply, so that criminal liability is refers to the doctrine of strict liability (absolute responsibility) and vicarious liability (responsibility imposed on another person) which in principle is a deviation from the principle of fault. This research was created and compiled using a narrative descriptive research method. This research typology is descriptive-narrative, emphasizing the use of secondary data obtained through literature study. In Article 59 of the Criminal Code, corporate criminal liability is borne by its management. Therefore, the subject of corporate criminal law is attached to the actions of the management themselves. The meaning of the claim in this case must be interpreted as a civil prosecution because the corporation loses the right to manage its assets which are entered into bankruptcy. Apart from that, if all of the corporation's assets are entered into bankruptcy, this will have an impact on the liquidation process. As stated in Article 71 POJK Number 28/POJK.05/2014, as well as Article 142 UUPT, it is possible for the liquidation process or the cause of liquidation to occur because of the bankruptcy decision.